2016
DOI: 10.1007/jhep02(2016)028
|View full text |Cite
|
Sign up to set email alerts
|

Boson stars from self-interacting dark matter

Abstract: We study the possibility that self-interacting bosonic dark matter forms starlike objects. We study both the case of attractive and repulsive self-interactions, and we focus particularly in the parameter phase space where self-interactions can solve well standing problems of the collisionless dark matter paradigm. We find the mass radius relations for these dark matter bosonic stars, their density profile as well as the maximum mass they can support.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
124
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 137 publications
4
124
0
Order By: Relevance
“…Similar ideas were independently investigated by many authors [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][40][41][42][43][44][45]. For example, a model with m = 0 was suggested in [27], which has a stability issue.…”
mentioning
confidence: 68%
“…Similar ideas were independently investigated by many authors [23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][40][41][42][43][44][45]. For example, a model with m = 0 was suggested in [27], which has a stability issue.…”
mentioning
confidence: 68%
“…The author found that, as its potential is unbounded from below, a star of this kind collapses all the way to its Schwarzschild radius and forms a black hole. Indeed, the leading axion self-interaction is attractive; axionic or other bosonic objects with repulsive interactions have been considered by [30,31]. However, the axion potential contains additional terms which become increasingly important as the axion density becomes large.…”
Section: Introductionmentioning
confidence: 99%
“…In that paper, we showed that one could find approximate solutions to these equations, by using a combination of analytical and numerical methods. We showed that our methods were numerically stable, and that they converged uniformly far away from the core of the star, and furthermore were much less computationally expensive compared to other purely numerical methods [18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 80%